A Systematic Mapping Study: What do We Know about Border Area Issues in International Relations? - Munir, Fitrisia; Yani, Yanyan Mochamad (Jurnal Hubungan Internasional, 2019)
Systematic mapping study (SMS) in this article is used to structure a research area and analyzed previous literature in International Relations with a research focus in border areas. The most recent guidelines for systematic mapping were in 2008. Meanwhile, there are needs for researchers including doctoral students to conduct the process of systematic mapping to find out a gap and novelty on research related to border areas. It comprises countries in Europe, America, and Asia, which are still on the limelight of the debates. This article aims to identify how the systematic mapping process is conducted (including search, study selection, analysis, and presentation of data, etc.) and improve potentials in conducting a systematic mapping process and updating the guidelines accordingly. The search was done on Scopus database online. SMS offers an overview and contributions to explore more new subjects in international border areas. It creates a map of current literature and can ensure helpful outcomes in practical use to identify gaps in future research. Researchers can use this study as a reference in conducting International Relations studies especially in developing the topics of border areas.